(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): Relationship between selected factors in the economic success of the company (return on equity) and the use of management tools. Purpose: To design a model of the impact of the use of manager’s tools on economic performance. Method: A quantitative survey in which we obtain data and information obtained through the questionnaire and search the public database of GVin. Results: Using the results of quantitative research we developed a conceptual model of the impact of the use of manager’s tools on economic performance. Organization: Based on the study of contemporary literature, comparisons of different has already carried out research and surveys of executive managers in large and medium-sized Slovenian companies, we formed the original model of the use of selected managerial tools on the profitability of capital companies. Society: Better business contributes to the long-term survival of companies and thus help to social welfare and better macroeconomic picture of the Slovenian economy. Originality: Based on the data obtained, we will gain new insights, knowledge and information on the use of selected tools managers. Limitations / further research: The survey will be carried out in large and medium-sized enterprises in Slovenia, we will discuss selected 25 management tools for Rigby-ROM, we will use data from publicly available databases.